Nonfiction: A Novel - Myerson, Julie (Portland, Oregon : Tin House, 2023)
"Two parents stand by powerlessly as their only child seems intent on destroying herself. As the mother--a novelist-attempts to understand her daughter, she finds herself revisiting her own uneasy, unresolved relationship with her mother. Weaving between childhoods past and present, laced with temptation and betrayal, Nonfiction: A Novel is an unflinching account of a mother, daughter, wife, and author reckoning with the world around her. But can a writer ever be trusted with the truth of her own story? Clear-eyed, lacerating, and fearless, Julie Myerson's Nonfiction: A Novel explores maternal love as an emotional foundation to both crave and fear. A hauntingly beautiful and deeply moving love letter from a mother to a daughter, this is a tale of damage and addiction, recovery and creativity, compassion and love"
Keywords: Mothers and daughters -- Fiction